A kötelességteljesítő protestáns etika, a szolgáló lelkület életpéldája. Balogh Jenő (1864–1953) jogászprofesszor személyes adatai és életútja - KOVÁCS, Gábor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
A Protestant Ethic of Duty, a Living Example of a Serving Spirit Biography of Law Professor Jenő Balogh (1864–1953) Our publication is part of a larger prosopographical study of the careers of Calvinist university professors belonging to the Hungarian knowledge elite in the bourgeois era (1848–1944). Jenő Balogh, a professor of law, was an academic researcher, a ministerial legislator seeking new paths, a teacher of modern disciplines, a minister in difficult times, and the General Secretary of the Academy. For decades, he held leading positions in the Calvinist Church of Hungary. His way of life and his work were determined by a Puritan Christian worldview brought from his family and by a dutiful Protestant ethic.